The press: Fourth power or counter-power? - Marsili, M. (2021)
The freedom of the press –or the freedom of expression –traces its roots in the enlightenment period. Oftenpresented as the "fourth power" – sometimes as "counter-power" –free press is considered a feature of liberal-democracies, and a fundamental human right.This brief article explores the validity of these definitions and the role of the press in democratic societies characterized by governments constrained by checks and balances. Most of this paper draws on my previously published works.